Feasibility Analysis of Clove Farming - Agnes Indan; Mukhammad Idrus; Samirah Dunakhir (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2025)
This study aims to evaluate the financial feasibility of clove farming in Lalonaha Village, Wolo District, Kolaka Regency. A descriptive quantitative approach was employed using primary data collected through interviews and documentation from 11 clove farmers. The analysis focused on production costs (fixed and variable), revenues, and profits, applying three key feasibility indicators: Revenue-Cost Ratio (R/C), Benefit-Cost Ratio (B/C), and Profit-Loss (L/R) analysis. The results show that clove farming in the study area is financially viable, with an R/C ratio of 23.19, a B/C ratio of 22.19, and an average annual profit of IDR 72,494,606 per farmer. These findings indicate that clove farming provides substantial returns relative to production costs and can be further developed as a sustainable agricultural enterprise. The study contributes to the literature on smallholder plantation economics by providing empirical evidence on the profitability of clove farming in Southeast Sulawesi, Indonesia.